Frequency of positive patch test reactions to preservatives: The Australian experience. (22nd October 2012) - Chow, Elizabeth T; Avolio, Andrea M; Lee, Adriene; Nixon, Rosemary
Abstract: Background/Objectives: Preservatives are important causes of allergic contact dermatitis. The frequency of allergy to preservatives in Australia has been unknown to date. Our objectives are to report the frequency of positive preservative patch test reactions in Australia, comparing them to the published international data, as well as exploring the current regulations in place for preservative use in Australia. Methods: This was the first retrospective study of patch testing results, aggregated from four patch test clinics in three centres in Melbourne and Sydney. Results: In all, 6845 patients were patch‐tested during 1993–2006 and in this period the five most frequent preservative allergens were formaldehyde (4.6%), Euxyl K400 (containing methyldibromo glutaronitrile and phenoxyethanol) (3.3%), quaternium‐15 (2.9%), diazolidinyl urea (2.4%), and methylchloroisothiazolinone/methylisothiazolinone (2.3%). These were followed by dimethylol dimethyl DMDM hydantoin (2.1%), chloroacetamide (2.1%) and imidazolidinyl urea (1.9%). The least frequent sensitisers were parabens (1.1%), 2‐bromo‐2‐nitropropane‐1, 3‐diol (0.9%) and benzyl alcohol (0.4%). Conclusions: Formaldehyde was the most prevalent preservative allergen. Chloroacetamide allergy was more commonly seen in Australia. Parabens, 2‐bromo‐2‐nitropropane‐1, 3‐diol and benzyl alcohol were the least frequent sensitisers. Household products in Australia are not required to list all ingredients preventing sensitised individuals from properly assessing their exposure.